Plasmid DNA analysis of pasteurella multocida Serotype B isolated from Haemorrhagic Septicaemia outbreaks in Malaysia - Jamal, H.; Chua, K.H.; Frederick, D.; Mahmood Ameen, A.; Salmah, I. (2005)
A total of 150 purified isolates of Pasteurella multocida serotype B were used (Salmah, 2004) for plasmid DNA curing experiment to determine hyaluronidase activity, antibiotic resistance pattern (ARP) and mice lethality test (LD50) for their role of pathogenicity. A plasmid curing experiment was carried out by using the intercalating agent; ethidium bromide and rifampicin, where it was found all the plasmids had been cured (plasmidless) from Pasteurella multocida. All of these plasmidless isolates maintained their phenotypic characteristics. They showed the same antibiotic resistancepattern as before curing, produced hyaluronidase and possessed lethality activity in mice when injected intraperitoneally(i.p). Based on this observation, the antibiotic resistance, hyaluronidase activity and mice virulence could probably be chromosomal-mediated. Plasmids were detected 100 in all P. multocida isolates with identical profile of 2 plasmids size 3.0 and 5.5 kb. No large plasmids could be detected in all isolates. Since all the isolates appeared to have identicalplasmid profiles, they were subjected to restriction enzyme(RE) analysis. From RE analysis results obtained, it can be concluded that the plasmid DNA in serotype B isolates are identical. Only 4 of 32 REs were found to cleave these plasmids with identical restriction fingerprints; BglII, HaeIII, RsaI and SspI. From RE analysis results, it can be concluded that the plasmid DNA isolates are identical. This plasmid might not played any role in pathogenicity of Pasteurella multocida serotype B, however this information is important for the construction of shuttle vectors in genetic studies of the pathogenicity of haemorrhagic septicaemia(HS).